The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnsys.2021.804263
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Analyses for the Causal Relationship Between Post-stroke Impairments and Functional Brain Connectivity Regarding the Effects of Kinesthetic Illusion Therapy Combined With Conventional Exercise

Abstract: Aims: Therapy with kinesthetic illusion of segmental body part induced by visual stimulation (KINVIS) may allow the treatment of severe upper limb motor deficits in post-stroke patients. Herein, we investigated: (1) whether the effects of KINVIS therapy with therapeutic exercise (TherEx) on motor functions were induced through improved spasticity, (2) the relationship between resting-state functional connectivity (rs-FC) and motor functions before therapy, and (3) the baseline characteristics of rs-FC in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Miyawaki et al's ndings 52 suggested that the impact of KI on upper limb motor function was mediated indirectly through its in uence on spasticity. In this study, the attention scores of participants during motor imagery tasks were displayed in real-time on a screen, providing them with visual feedback of their brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Miyawaki et al's ndings 52 suggested that the impact of KI on upper limb motor function was mediated indirectly through its in uence on spasticity. In this study, the attention scores of participants during motor imagery tasks were displayed in real-time on a screen, providing them with visual feedback of their brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, visual-motor illusion (VMI), in which kinesthetic sensation is induced by visual stimulation, has been reported to be effective in improving motor function in hemiplegic patients [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. VMI induces the illusion of movement in the subject’s limbs, even though they are not moving, by overlaying an image showing the movements of the limbs on the actual subject’s limbs for observation [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of SoO and the degree of brain network activation are reported to be greater with VMI than with AOT [ 21 ]. Numerous previous reports have indicated that VMI led to improved upper limb function in hemiplegic patients [ 8 , 9 , 10 , 11 , 12 ]. In addition, for paralyzed ankle joints, VMI has led to an increase in the voluntary ankle dorsiflexion angle, suppression of muscle tone in the antagonist muscle, and improvement in standing movements and walking ability [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%